“Quis Custodiet Ipsos Custodes?” The Federal Reserve System's Founding Fathers and Allied Finances in the First World War - Roberts, Priscilla (Business History Review, 1998)
The First World War presented the newly formed Federal Reserve System with issues that were crucial in defining its future institutional character and operational strategies and priorities. From 1914 to 1917 disputes over the relationship between the U.S. and belligerent European nations divided competing groups of New York bankers who had helped to create the Federal Reserve System and who otherwise shared many of the same objectives for its future purpose and functions. These divisions grew particularly acrimonious over policies concerning acceptances, a new financial instrument that could substantially affect the Allied powers' ability to obtain war funding in the United States. Despite these wartime splits, the rival financial groups, led by Benjamin Strong and Paul M. Warburg, generally concurred in assigning a higher priority to the international implications of Federal Reserve policies than to domestic consequences. Likewise, after the war both united in using the Federal Reserve System to facilitate Europe's economic recovery.
Keywords: Business History and gender